Benzyne arylation of oxathiane glycosyl donors - Fascione, Martin A.; Turnbull, W. Bruce (Beilstein Journal of Organic Chemistry, 2010)
The arylation of bicyclic oxathiane glycosyl donors has been achieved using benzyne generated in situ from 1-aminobenzotriazole (1-ABT) and lead tetraacetate. Following sulfur arylation, glycosylation of acetate ions proceeded with high levels of stereoselectivity to afford α-glycosyl acetates in a ‘one-pot’ reaction, even in the presence of alternative acceptor alcohols.
Keywords: benzyne; 1,2-cis-glycosides; glycosyl acetates; oxathiane glycosyl donors; stereoselective glycosylations